PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN SALES FORCE PADA PT TELKOM (Persero) CABANG KENDARI - Meitri, Jeanet Silky; Nurwati, Nurwati; Montundu, Yusuf; Kamaluddin, Murdjani; Yusuf, Yusuf (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to determine simultaneously and partially the effect of Work Motivation and job satisfaction on the performance of sales force employeesof PT Telkom (Persero) Kendari Branch. The population selected in this study were employees as sales force at PT Telkom (Persero) Kendari Branch totaling 63 employees. This type of research data is quantitative data research. The data source used in this research is primary data. Variable measurement scale using an instrument using a Likert scale. The data analysis method of this research is multiple linear regression. The results showed that simultaneously and partially work motivation and job satisfaction had a positive and significant effect on employee performance.